Economic Development and Innovation at Local Level – Local Business Environment Index (LBEI) - Clara Volintiru; Mihai Volintiru; George Ștefan (Romanian Journal of European Affairs)
This paper presents a novel metric for assessing economic activity at local level: Local Business Environment Index (LBEI). In the development of this metric system we explore a large set of variables that are disaggregated at municipal level for the case study of Romania. Following the existing literature on the different drivers of economic development, we propose four major axes of assessment: entrepreneurship, innovation, investment financing, and public authorities’ support. We present the overall ranking of the level of attractiveness of the local business environment in the Romanian municipalities, among which the highest scores belong to cities of various sizes: Bucharest, Cluj-Napoca, Timișoara, Alba-Iulia and Sibiu. Each municipality has a different distribution of specific strengths. We look in-depth in the final section of this paper at the sub-index of Innovation, dominated by Timișoara or Cluj, rather than the capital city.